Influence of Plant Spacing and Fertilizer Dose on Yield Parameters and Yield of Sweet Corn (Zea mays L.) - Shanti, J.; Sreedhar, M.; Durga, K. Kanaka; Keshavulu, K.; Bhave, M. H. V.; Ganesh, M. (International Journal of Bio-resource and Stress Management, 2023)
An investigation was carried out to study the influence of plant spacing at four levels, viz. 45x15 cm2, 45x20 cm2, 60x15 cm2 and 60x20 cm2 and fertilizer doses at three levels, i.e. 90: 45: 45 NPK kg ha-1, 120: 60: 45 NPK kg ha-1 and 150: 75: 45 NPK kg ha-1 on sweet corn during kharif 2008. Significance of fertilizer dose was observed for number of seed rows cob-1 and number of seeds cob-1, while plant spacing was significant for shelling percentage. Interaction between plant spacing and fertilizer dose was found to be significant for various parameters, viz. cob girth and length, number of seeds cob-1, shelling percentage, 100 seed weight and seed yield plant-1. Combinations, viz. 45x20 cm2 and 120: 60: 45 NPK kg ha-1, 60x15 cm2 and 150: 75: 45 NPK kg ha-1, 60x20 cm2 and 120: 60: 45 NPK kg ha-1, 60x20 cm2 and 150: 75: 45 NPK kg ha-1, performed better for yield components like cob girth and length, number of seeds cob-1 and 100 seed weight thus, higher seed yield plant-1. Similar performance of 45x20 cm2 /120:60:45 NPK kg ha-1 with other superior combinations indicated the field value of lower plant spacing and moderate fertilizer dose in realizing higher seed yield.